Ying and yang of urocanic acid in skin pathogenesis: a mini review on its metabolism and effects - Ali Musa, Aina Yusrina; Abdul Hamid, Hisyam; Husain, Noreen (Faculty of Pharmacy, 2025)
Urocanic acid (UCA) is a main chromophore responsible for absorbing ultraviolet (UV) radiation in the epidermis, particularly in the stratum corneum. It exists naturally as trans-UCA in the skin and undergoes photoisomerization to cis-UCA when exposed to UV radiation. It exerts diverse impacts on the health and diseases of the skin. This review aims to enhance our comprehension of the role of cis-UCA by examining its biological functions, therapeutic potential and pathological implications with a particular focus on its involvement in immune modulation, skin barrier function and oxidative stress response by highlighting existing knowledge gaps, novel experimental approaches, and future research. Previous research has extensively studied the immunomodulatory effects of cis-UCA and its role in maintaining skin barrier function. Additionally, its involvement in numerous pathological disorders such as skin cancer, skin allergies, and photoaging has also been extensively examined. Recent studies have revealed the potential therapeutic uses of cis-UCA, including its application in sun protection and skin disease therapy. Despite some notable progressions, the exact mechanisms and pathways by which cis-UCA produces its effects are not completely comprehended, thus requiring further investigation. This review also discusses the most recent research trends, emerging technologies, and prospects in the study of cis-UCA, intending to offer a thorough overview that highlights the significance of this molecule in the field of skin issues.